Antifungal Activity of Sodium New Houttuyfonate Against Aspergillus fumigatus in vitro and in vivo - Zhang, Qian; Liu, Fangyan; Zeng, Meng; Zhang, Jinping; Liu, Yanfei; Xin, Caiyan; Mao, Yingyu; Song, Zhangyong (Frontiers in Microbiology, 2022)
Aspergillus fumigatus is an important pathogen causing invasive aspergillosis, which is associated with high morbidity and mortality in immunocompromised people. However, the treatment of A. fumigatus infection is a growing challenge, owing to the limited availability antifungal agents and the continual emergence of drug-resistant strains. Drug repurposing is a potential strategy to solve this current problem. Sodium new houttuyfonate (SNH), derived from houttuynin, extracted from Houttuynia cordata, has anti-bacterial and anti-Candida albicans effects. However, whether it has anti-A. fumigatus activity had not been reported. In this study, the antifungal properties of SNH against A. fumigatus, including the standard strain AF293, itraconazole resistant clinical strains, and voriconazole resistant clinical strains, were evaluated in vitro and in vivo. Moreover, the potential mechanism of SNH was characterized. SNH exhibited significant fungicidal activity toward various A. fumigatus strains. SNH also inhibited fungal growth, sporulation, conidial germination and pigment formation, and biofilm formation. Further investigations revealed that SNH interfered with the A. fumigatus cell steroid synthesis pathway, as indicated by transcriptomic and quantitative real-time polymerase chain reaction analyses, and inhibited ergosterol synthesis, as indicated by cell membrane stress assays and ergosterol quantification. Moreover, daily gastric gavage of SNH significantly decreased the fungal burden in mice with disseminated infection (kidney, liver, and lung) and local tissue damage. In addition, the application of SNH downregulated the production of IL-6 and IL-17A. Together, these findings provided the first confirmation that SNH may be a promising antifungal agent for the treatment of A. fumigatus infection.